Seismic Behavior Investigations of the Haunched Joint with Ribbed Anchor Webs in CFDST Structures - Yufen Zhang; Xiaokun Qu; Ling Wang; Hongfan Bu; Shengxi Cao (Advances in Civil Engineering)
The haunched joint with ribbed anchor webs in the concrete-filled double steel tubular (CFDST) structure was proposed in this study. The CFDST column and the steel beam were connected by ribbed webs, which were anchored inside the column and connected to the beam web by the bolted connection, and haunches were welded to shift plastic hinges from the joint core to the beam end. The cyclic loading test was conducted on three beam-to-column joint specimens. Seismic behaviors, including failure modes, strain and stress responses, hysteretic curves, ductility, and energy dissipation capacity, were, respectively, analyzed. Besides, finite element (FE) modeling was validated and was used to further analyze the seismic behavior in consideration of connection constructional details, geometric dimensions, material strength, and axial compression ratios. The parametric investigation shows that besides ribs and haunches, stiffening diaphragms are practicable to connect the double tubes, especially for the high-strength steel beam; beam-to-column bending stiffness ratio per unit length is appropriate to be 0.3–0.5; choosing low strength grade of concrete is allowed to satisfy engineering requirements; the axial compression ratio should be limited within 0.5.